Cerebrovascular events after transcatheter mitral valve interventions: a systematic review and meta-analysis. Issue 22 (17th April 2020) - Châteauneuf, Gabriel; Nazif, Tamim M; Beaupré, Frédéric; Kodali, Susheel; Rodés-Cabau, Josep; Paradis, Jean-Michel
Abstract : Objective: Current guidelines support the use of transcatheter mitral valve interventions to treat some selected high-risk patients with significant mitral valvulopathy. As with any other interventional cardiac procedure, concerns have been raised about cerebrovascular event. The aim of this systematic review and meta-analysis was to determine the incidence of cerebrovascular events following (1) transcatheter mitral valve edge-to-edge repair with mitral valve clip and (2) transcatheter mitral valve replacement (TMVR). Methods: We conducted a systematic review of studies reporting the cerebrovascular adverse events after transcatheter mitral valve edge-to-edge repair and TMVR procedures. The primary endpoint was the incidence of cerebrovascular events as defined by the Mitral Valve Academic Research Consortium. An event that occurred within 30 days or during index hospitalisation was defined as periprocedural; otherwise it was defined as non-periprocedural. This study was designed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Aggregated study-level data were pooled using a random effect model. The quality of each study was appraised with the Hawker checklist, a method of systematically reviewing research from different paradigms. Results: Sixty studies totalling 28 155 patients undergoing edge-to-edge repair with mitral valve clip were included in the analysis. Periprocedural stroke and non-periprocedural stroke rates were 0.9% (95% CI 0.6 to 1.1) and 2.4% (95% CI 1.6 to 3.2), respectively. For TMVR procedures, 26 studies including 1910 patients were analysed. The estimated periprocedural stroke incidence was 1% (95% CI 0.5 to 1.8) compared with 7% (95% CI 0.8 to 18.5) for non-periprocedural stroke. Conclusions: Transcatheter mitral valve interventions are associated with low rates of cerebrovascular events. The exact mechanisms of these complications are still poorly understood given the relative paucity of good quality data. Trial registration number: CRD42019117257.